Tekanan Kepemilikan Saham Pada Audit Delay Di Bursa Efek Indonesia Periode 2016-2019 - Baniady Gennody Pronosokodewo; Rahandhika Ivan Adyaksana (Journal of Applied Accounting and Taxation, 2021)
Shareholders want audited financial reports to be published immediately to make precise and accurate economic decisions. Companies were late in publishing audited financial reports can indicate bad news in the company's financial statements. The delay in submitting financial reports can be said to be the length of the company's audit delay, which resulted in the company being sanctioned by the OJK (submission of financial reports should not exceed 31 March). This study aims to analyze whether share ownership consisting of public ownership, institutional ownership and managerial ownership can affect audit delay in companies listed on the IDX during 2016-2019 period. This research uses secondary data from companies that are included in the LQ45 category with purposive sampling method and obtained a sample of 77 companies during 2016-2019. The research hypothesis was tested using SEM method, the statistical tool namely Warp PLS. The results of this study is public ownership has a negative effect on audit delay, institutional ownership has a positive effect on audit delay, and managerial ownership has no effect on audit delay.